Control of scara robot using fuzzy–neural algorithm - Huynh , Minh Vũ; Tran, Thanh Hùng; Nguyen, Chí Ngôn (Journal of Technical Education Science, 2019)
This paper aims to verify the expert’s ability to learn behavioral control based on adaptive fuzzy - neuro inference systems (ANFIS). To simulate the control behavioral of experts, a fuzzy-PID controller for SCARA robot has been built. By a training mechanism, ANFIS controller can operate independently, after learning from an expert control data. A SCARA robot is selected to verify this idea. This is a multi-input multi-output (MIMO) nonlinear system which is relatively difficult to control. The simulation results on MATLAB show that the controller using ANFIS can be used to learn expert control data, creating a foundation for building controllers that have the capacity to learn people behavior.